1994
DOI: 10.1139/y94-219
|View full text |Cite
|
Sign up to set email alerts
|

Body-core temperature decreases during hypoxic hypoxia in Long–Evans and Brattleboro rats

Abstract: In newborn mammals, hypoxic hypoxia produces a regulated decrease in body-core temperature, the mechanism of which is unknown. Since plasma and cerebrospinal fluid levels of arginine vasopressin increase during hypoxemia and intracerebroventricular administration of arginine vasopressin decreases body-core temperature, it has been hypothesized that an increase in central arginine vasopressin may mediate this response. Experiments were therefore carried out to test the hypothesis that the body-core temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Similar results have been observed for vasopressin, which, like lactate, increases in plasma and in cerebrospinal fluid during hypoxia [13,26] and also reduces T c when administered to mammals [21,27,31]. However, studies on Brattleboro rats (that lack vasopressin-producing neurons in the central nervous system) and vasopressin antagonists in Wistar rats have shown that rats develop anapyrexia regularly in response to hypoxia in the absence of vasopressin [9] or when its receptors are blocked [32].…”
Section: Discussionsupporting
confidence: 74%
“…Similar results have been observed for vasopressin, which, like lactate, increases in plasma and in cerebrospinal fluid during hypoxia [13,26] and also reduces T c when administered to mammals [21,27,31]. However, studies on Brattleboro rats (that lack vasopressin-producing neurons in the central nervous system) and vasopressin antagonists in Wistar rats have shown that rats develop anapyrexia regularly in response to hypoxia in the absence of vasopressin [9] or when its receptors are blocked [32].…”
Section: Discussionsupporting
confidence: 74%
“…However, there is only one published study (7) that evaluated the participation of AVP in hypoxia-induced anapyrexia, in which AVP does not seem to mediate the reduction in T b . In that study, anapyrexia was similar in both Brattleboro rats (which lack AVP-containing cells in the central nervous system) and Long-Evans rats (used as a control) (7). However, thermoregulation may be aberrant in Brattleboro rats.…”
mentioning
confidence: 88%
“…The effects of the V1 antagonist on baseline core temperature suggests that V1 receptors could be involved in tonic thermoregulatory processes. It is also interesting to note that several studies have found that the V1 antagonist does not block hypoxic‐induced hypothermia in the rat ( Clark & Fewell 1994 ; Steiner et al , 1999 ). That cholinergic stimulation is critical in the chlorpyrifos‐induced but not hypoxic‐induced hypothermia suggests that cholingergic‐induced vasopressin release is operative in the former but not the latter.…”
Section: Discussionmentioning
confidence: 97%